Usulan Penerapan Lean Six Sigma dan FMEA (Failure Mode and Effect Analysis) dalam Upaya Pengendalian Kualitas Produk Roti Meses: Studi Kasus UD. Sarigut Bakery - Mika Sri Wahyuni (Pusat riset dan Inovasi Nasional, 2025)
UD. Sarigut Bakery is known as one of several industries that focus on processing bread specifically in the Banda Aceh City area that seeks to produce with a variety of bread. The purpose of this study is to carry out efforts to identify, measure efforts, and analyzing efforts to the phase known to be the cause of the decline in quality of the production process of meses bread through a series of stages of the DMAIC SIX SIGMA methodology. It is known that the main problem is the discovery of disability with a total of 4,096 of the total production of the production of 21896 with a period of 3 months specifically in the dominant disability of Meses bread in the percentage of 81.29%. With the dominant of the disability itself the disability that comes in damaged bread with a percentage of 36.49% present from all of the total disability of related meses bread. After the assessment effort, the DPMO value was obtained by 26723.74 so that there were several levels of Sigma 3, which means it was still far from the world industry level which reached 6σ (3.4 DPMO). Efforts to analyze the data carried out by applying the Fishbone and FMEA (Failure Mode and Effect Analysis) diagrams are known to be related to the cause of the presence of disability from damaged bread with 3 modes of failure in potential, namely bread that is not filled with chocolate with a value of 20, the upper bread with a value of RPN of 80 and failure mode on broken bread with the highest RPN value of 90.